تقريب الدوال العقدية من فضاء ليبيغ الموزنL_p (Γ,V) على منحنيات كارلسون (Latakia University Journal -Basic Sciences Series, 2016)
درسنا في هذا البحث مسألة تقريب الدوال العقدية من فضاء ليبيغ الموزن حيث              و  (وزن ماكنهوبت)، إلى دوال كسرية متعلقة بكثيرات حدود p – فابير وذلك على أسرة واسعة من المنحنيات تدعى منحنيات كارلسون، كما ويعد هذا العمل بمثابة متابعة لما قام به الباحثان Israfilov و Testici عام 2014 في [4]، حيث درسا تقريب الدوال العقدية من فضاء سميرنوف الموزن  على مناطق  محاطة بمنحنيات كارلسون.In this research, we have studied the issue of approximation of complex functions from weighted Lebesgue space ;  and  (Mukenhoupt weight) to rational functions by using p- Faber polynomials on large group of curves, which called Carlson curves. This is also considered as a follow-up to the work done by researchers: Israfilov and Testici in 2014 [4], where they studied approximation of functions from weighted Smirnov space  on domains  with a Carlson curve boundary.